More summits than mountains - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
It s the Year of the Mountain, but it s not just the summits of Mount Kilimanjaro, the Blue Mountains and the highlands of Papua New Guinea which are getting crowded these days. Take a look at the diaries of the world s political leaders ...